WOMEN EMPOWERMENT AND MICRO FINANCE IN KERALA - IRSHAD M K and R.Sathyadevi (International Journal of Scientific Engineering and Applied Science (IJSEAS) -, 2015)
The subject of micro-finance is considered as significant and emerging trend in the present scenario for the empowerment of women. Micro finance programmes are promoted as an important strategy for women’s empowerment. Micro finance builds mutual trust and confidence between bankers and rural poor to encourage banking in a segment of population where formal financial institutions usually find difficult to reach. The present paper examines the economic impact of micro finance beneficiaries and whether the economic empowerment has resulted in the generation of a set of self reliant women. The study shows about the positive impact of the development programme of Kudumbashree, a micro financial institution in Kerala, India.